Adaptive Reuse of Abandoned Industrial Structures for Healthcare Centres - Zoha Mirza; Saksham K. Verma (International Journal of Architectural Design and Planning, 2024)
Adaptive reuse as an industry has been marketed as an expensive one. When it comes to the retail, hospitality, or domestic sectors, that is the case; however, the use of abandoned structures has been found to be cost-effective in the healthcare sector. This research paper aims to understand adaptive reuse in the context of the healthcare industry. It is a well-known fact that the worldwide epidemic drove the economy to decline, which led to several industrial set-ups being abandoned. Re-functionalizing these buildings offers a great chance for social and economic advancement. To fulfil the purpose of this research, case studies were reviewed. This review helped identify a number of factors that need to be considered while choosing an industrial abandoned site for adaptive reuse. These abandoned sites can no longer be used for their initial functions and hence can be used to be redesigned for a new purpose, especially for healthcare considering the state of infrastructure or lack thereof. But the research regarding the reuse of abandoned industrial structures for the healthcare division is scattered. Based on the gaps identified through the case studies, a study was conducted which helped answer these concerns. This research paper attempts to study the opportunities and obstacles that arise in an adaptive reuse project, analyse, and compile the data for the same. By doing so, an operational framework can be derived, which will provide useful insights and make the process of adaptive reuse of abandoned industrial sites for healthcare easier
Keywords: abandoned structures; adaptive reuse; factors for site selection; healthcare centres; industrial structures